Humor and Its Relationship to Students’ Assessments of the Counsellor - Foster, James A.; Reid, Jane (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this study was to examine the use of humor in counselling. Students viewed a videotaped simulated counselling session containing either facilitative counsellor humor, non-facilitative humor, or no humor and then ratedthe counsellor on four dimensions. The results indicated that non-facilitative humoris less desirable than facilitative humor or no humor at all in terms of counsellor likableness, approachability, or ability to create rapport but not in terms of client understanding. Ratings were unaffected by sex of the rater.